Ecotoxicity and environmental fate of diesel and diesel blends produced by Sasol’s Fischer-Tropsch processes using natural gas and coal as feedstock as well as biodiesel and biodiesel blends - Albertus, Randal Marius Colin (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.